Exploring galaxy evolution with luminosity functions across cosmic time - Elbert, H (2016)
In this thesis I investigate galaxy evolution by measuring the luminosity functions of galaxies across a wide range in redshift. I measure the abundances of high redshift galaxies in deep HST imaging of the GOODS-North field from the CANDELS survey. I follow this evolution to lower redshift by measuring the luminosity functions of galaxies in ground-based imaging of the XMM-LSS field from the VIDEO survey with optical data from the CFHTLS. First, at high-redshift, I identify 22 candidate z ≈ 7 and 6 candidate z ≈ 8 − 9 galaxies. By comparing the number of candidate galaxies with those found in the GOODS-South field, I determine that cosmic variance is not the dominant source of uncertainty on the number counts. I constrain the Schechter parameters for the UV luminosity function at z ≈ 7 and z ≈ 8 − 9, finding evidence for evolution in the number density of high redshift galaxies. Next, I present the Ks-band luminosity functions in the 1 degree2 and 4.5 degree2 overlaps between the VIDEO-XMM field and the CFHTLS-D1 and CFHTLS-W1 fields. I measure the luminosity functions with the 1/Vmax method over the range 0.2 < z < 3 in VIDEO-CFHTLS-D1, and over the range 0.2 < z < 1.5 in the shallower VIDEO-CFHTLS-W1 field. I find the evolution of these luminosity functions is best described by luminosity dependent density evolution, where the characteristic magnitude has dimmed at a constant rate since z = 3, while the density has increased since z = 3, first rapidly from z = 3 to z ≈ 1.5 and then more slowly from z ≈ 1.5 to z = 0.2. I measure a significant upturn at the faint end of the luminosity function at low redshift. Finally, I compare the VIDEO-CFHTLS-D1 and VIDEO-CFHTLS-W1 luminosity functions with predicted K-band luminosity functions from the Horizon-AGN simulation. I find both an over-prediction in the numbers of faint galaxies and an under-prediction in the numbers of bright galaxies, implying that the feedback from supernovae is insufficient while the feedback from AGN is over-sufficient.